2013
DOI: 10.1177/1941738112473053
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Injury Characteristics of Medial Collateral Ligament Injuries in Male Collegiate Ice Hockey Players

Abstract: Background:Medial collateral ligament (MCL) injuries are the second most common injury resulting in player lost time in elite-level ice hockey.Purpose:To determine the incidence and injury characteristics of knee MCL sprain in male collegiate ice hockey players.Study Design:Case control.Methods:Athlete exposure data demographics, mechanism of injury, player position, time of injury occurrence (game vs practice), grade of MCL sprain, concomitant injuries, and lost time for cases were extracted from a computeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…8,36 Although not extensively studied, it has been previously suggested that differential age (freshman vs senior), experience, skill level, and history of musculoskeletal injury between competitors is associated with MCL injury risk. 37 It has been noted in ice hockey players that preseason functional movement screens such as postural analysis, single-leg stance, hip mobility, pelvic alignment, and squat screen are likely to aid in identifying athletes at greater risk of sustaining a MCL tear. 38 In contrast to preventative techniques, the efficacy of prophylactic knee bracing has been observed to have little effect in reducing the risk of this injury in ice hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…8,36 Although not extensively studied, it has been previously suggested that differential age (freshman vs senior), experience, skill level, and history of musculoskeletal injury between competitors is associated with MCL injury risk. 37 It has been noted in ice hockey players that preseason functional movement screens such as postural analysis, single-leg stance, hip mobility, pelvic alignment, and squat screen are likely to aid in identifying athletes at greater risk of sustaining a MCL tear. 38 In contrast to preventative techniques, the efficacy of prophylactic knee bracing has been observed to have little effect in reducing the risk of this injury in ice hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…Medial collateral ligament (MCL) injuries, in particular, are the second most common injury after concussions in collegiate-level players and the third most common injury to result in significant time loss from competition. 78 The knee is put through the full range of motion during fast skating with the optimal stride technique requiring significant knee flexion and near-complete extension. Abrupt changes in direction can result in varus, valgus, and twisting forces that result in the most common injuries around the knee: MCL, meniscal, and anterior cruciate ligament (ACL) tears.…”
Section: Knee Generalmentioning
confidence: 99%
“…1,80 MCL injuries have a similar incidence in forward and defense positions. 78 Many MCL injuries are related to player contact; noncontact injury due to catching an edge only accounts for 15% of cases. 78,81 MRI is the definitive imaging study for assessment of MCL injuries that are graded similarly to other ligamentous injuries (►Fig.…”
Section: Knee Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The MCL is susceptible to injury as a result of an ice collision causing a valgus stress to the knee or from a player catching a skate on the ice with a twisting force 40. MCL injury can result in substantial time lost from the ice rink 9,55. There are three grades of injury to the MCL.…”
Section: Kneementioning
confidence: 99%